The case number 52 of Ruprecht Majewski-Bosma syndrome associated with atrial septal defect - Aamir Jalal Al Mosawi (Global Journal of Rare Diseases - Peertechz Publications, 2020)
Background: Ruprecht Majewski-Bosma syndrome is an extremely rare dysmorphic syndrome results from severe hypoplasia of the nose and eyes occurring in association with palatal abnormalities. It is characterized by congenital complete nasal agenesis (Bilateral aplasia of the nose), microphthalmia including clinical anophthalmia, hypertelorism and other eye defects, high arched palate, and other palatal defects. Materials and methods: A full term newborn female born to a consanguineous parents in their twenties with multiple congenital abnormalities was observed and studied at Children Teaching Hospital of Baghdad Medical City. The relevant literature was reviewed. Results: At birth the girl had the characteristic congenital abnormalities Ruprecht Majewski-Bosma syndrome of including complete nasal agenesis (Bilateral aplasia of the nose), bilateral microphthalmia, high arched palate, hypertelorism, and secondum atrial septal defect. Conclusion: Literature review confirmed the extreme rarity of the condition. Becerra-Solano et al. (2016) reported the fiftieth case of the syndrome in the literature. The case of Mondal and Prasad was most probably the case number fifty-one. Congenital heart defects have not been reported in association with this syndrome. The paper reported the fifty second patient with Ruprecht Majewski-Bosma syndrome which is the first case of the syndrome to be associated with congenital heart defect, atrial septal defect.